Dislocation and Resettlement in Development: From Third World to the World of the Third - Chakrabarti, Anjan; Dhar, Anup Kumar (Routledge Studies in Development and Society, 2010)
Challenging the more conventional approaches to dislocation and resettlement that are the usual focus of discussion on the topic, this book offers a unique theory of dislocation in the form of primitive accumulation. Interrogating the ‘reformist-managerial’ and ‘radical-movementist’ approaches, it historicizes and politicizes the event of dislocation as a moment to usher in capitalism through the medium of development. Such a framework offers alternative avenues to rethinking dislocation and resettlement, and indeed the very idea of development. Arguing that dislocation should not be seen as a necessary step towards achieving progress - as it is claimed in the development discourse - the authors show that dislocation emerges as a socio-political constituent of constructing capitalism. This book will be of interest to academics working on Development Studies, especially on issues relating to the political economy of development and globalization. 1. Debates on Dislocation, Compensation and Resettlement: What Does Our Approach Contribute? 2. Development and Dislocation: Why one Cannot be Addressed Without the Other? 3. From ‘Compensation’ to ‘Resettlement Need’: The Reformist-Managerial Approach 4. De-Familiarising the Economy and Development 5. A Critique of Received Theories of Dislocation, Compensation and Resettlement 6. Western Marxism and its Theory of Primitive Accumulation: Limits and Limitations 7. Primitive Accumulation – World of the Third Marxian Perspective on Dislocation 8. Two Case Studies of Primitive Accumulation in India: Special Economic Zone and Plachimada 9. From Resistance to Resettlement Right: Confronting the ‘Subjects of Development’ and Policy Paradigms Anjan Chakrabarti is Professor in the Department of Economics at the University of Calcutta, India. His publications most recently include (as co-author) Transition and Development in India (also published by Routledge). Anup Kumar Dhar is Associate Fellow at the Centre for the Study of Culture and Society (CSCS), Bangalore, India. As co-authors, they recently published Global Capitalism and World of the Third .